The paradigm of aggression as the basis for the modernization of international law-making - KAMINSKA Наталія; GDYCHYNSKY Віталій (Ius Modernum, 2025)
Attention has been drawn to the analysis of the modern paradigm of aggression, its essential characteristics, as well as the natural modernization of international law-making and the novelization of international legal regulation in this direction. The main components are identified as follows: 1) an analysis of the conceptual foundations of the study of the aggression paradigm, including the consideration of pluralistic methodological tools and modern interpretations; 2) the results of a critical study of the state of international legal regulation of aggression, emphasizing the need for its modernization and strengthening responsibility for the implementation of various forms of manifestations of aggression etc. The multidimensional and interdisciplinary nature of the modern paradigm of aggression is justified, along with the evolutionary character of the formation of the basis for international legal regulation. Currently, the definition of aggression is recorded in UN General Assembly Resolution 3314 (XXIX) "Definition of Aggression" from 1974, the Rome Statute of the International Criminal Court from 1998, although aggression, aggressive war, and other forms of it are also mentioned in other international acts as well. It is emphasized on the ambiguous understanding of aggression, the differences in interpretation in the classical sense and the modern one, considering certain modifications of current aggressions, including the aggression of the russian federation against Ukraine, its hybrid forms of manifestation (military, economic, informational, cultural, etc.). It is important to expand the subject composition of aggression and to search for optimal effective mechanisms for holding accountable those who commit it. It is emphasized that the complexity and ineffectiveness of existing tools for countering aggression, bringing perpetrators to justice for their actions, the growth of challenges and threats, the increase in forms of aggression, and the failure to meet the goals of the UN and other international organizations, determine the expediency of modernizing international legal regulation, ensuring timely and fair punishment for acts of aggression. Both in international law and in the national legislation of democratic states, proper scientifically justified regulation and implementation of effective measures of countering aggression, any aggressive manifestations and threats are necessary for the stable functioning of national and international legal orders, and for ensuring international peace and security for mankind.